2007
DOI: 10.1212/01.wnl.0000271387.10404.4e
|View full text |Cite
|
Sign up to set email alerts
|

Primary collagen VI deficiency is the second most common congenital muscular dystrophy in Japan

Abstract: Primary collagen VI deficiency is the second most common CMD after Fukuyama type CMD in Japan. Dominant mutations located in the N-terminal side from the cysteine residue in the THD of COL6A1, COL6A2, and COL6A3 are closely associated with SSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 29 publications
5
96
1
1
Order By: Relevance
“…Skipping of COL6A3 exon 16, due to splice site mutations or small deletion, is the most common molecular defect in dominant UCMD patients (11,13,23,25). In this study we deleted exon 16 and its flanking sequence in the mouse Col6a3 gene by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skipping of COL6A3 exon 16, due to splice site mutations or small deletion, is the most common molecular defect in dominant UCMD patients (11,13,23,25). In this study we deleted exon 16 and its flanking sequence in the mouse Col6a3 gene by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we generated a mutant mouse bearing the most common molecular defect found in dominant UCMD patients, i.e. skipping of exon 16 in the COL6A3 mRNA (11,13,23,25). We show that mutant mice heterozygous for the Col6a3 exon 16 deletion, named…”
mentioning
confidence: 99%
“…The concept of a spectrum of collagen VI-related disorders with marked clinical and genetic heterogeneity has emerged from the recent advances on the molecular mechanism of both diseases 69 . The complex genotype/phenotype correlations that have been broadly analysed in these two conditions clearly indicate that in both collagen VI-related disorders the main pathomechanism is due to the disruption of collagen VI anchorage to the basal lamina of the muscular fibers 74,75,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] .…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
“…In conclusion, they demonstrated that in patients with different dominant glycine mutations a mild phenotype is associated to a mild assembly defect whereas severe assembly defects result in moderate-to-severe phenotype. okada et al 138 found that in Japanese population mutations in collagen VI genes can lead to a collagen VI deficiency in the sarcollema (where normally it is strongly delineated) but with apparently normal amount in the interstitium. They sequenced the three collagen VI genes in Congenital muscular dystrophy: Part II reed 26 Japanese patients with primary collagen VI deficiency that in Japan accounts for 7.2% of CMD cases.…”
Section: Collagen VI Related Muscle Disorders Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation